Does autoimmune vitiligo protect against COVID‐19 disease?. Issue 9 (17th June 2021) - Post, Nicoline F.; Luiten, Rosalie M.; Wolkerstorfer, Albert; Bekkenk, Marcel W.; Böhm, Markus
Abstract: The SARS‐CoV‐2 pandemic has evolved to a global health problem with a dramatic morbidity and mortality rate impacting our daily life and those of many patients. While there is evidence that some diseases are associated with an increased risk for development of a more severe course of COVID‐19, little is known on protective conditions. Importantly, clearance of viral infection and protection against disease manifestation crucially depends on functional innate and adaptive immunity and the interferon signalling axis. Here, we hypothesize that patients with non‐segmental vitiligo (NSV), an autoimmune skin (and mucosal) disorder, may clear SARS‐CoV‐2 infection more efficiently and have a lower risk of COVID‐19 development. Conversely, in case of COVID‐19 development, vitiligo autoimmunity may influence the cytokine storm‐related disease burden. In addition, immune activation during SARS‐CoV‐2 infection or COVID‐19 disease might increase vitiligo disease activity. Our hypothesis is based on the shift of the immune system in NSV towards adaptive type 1 (IFNγ and CD8 T cells) and innate immune responses. Identified susceptibility genes of NSV patients may further confer increased antiviral activity. To validate our hypothesis, we suggest an international consortium to perform a retrospective data registry and patient‐reported study on a large number of NSV patients worldwide during the COVID‐19 pandemic.